Experience of conducting academic classes using distance learning technologies at Ukrainian engineering pedagogics academy (using the example of sewing profile specialties) - Popova, T.; Nechipor, S. (Problems of Engineer-Pedagogical Education, 2023)
Taking into account the peculiarities of the introduction of martial law on the territory of Ukraine and constant missile attacks on the city of Kharkiv, face-to-face training in this city is currently impossible. Therefore, in fact, distance learning is becoming the main form of education in the city of Kharkiv. Ukrainian Engineering Pedagogics Academy (UEPA) has chosen the Moodle platform for distance learning, the use of which allows students to stay and study in a safe environment, provides access to the necessary educational and methodological literature in the electronic form at a time convenient for learning, expands the opportunities for independent work of students, and ensures constant monitoring of their knowledge and skills through the use of online testing tools, independent practical assignments, etc. In addition to distance learning, the Google Meets service on the Google browser is used to ensure communication between students and teachers during lectures, practical, laboratory and seminar classes. A distance learning course for any discipline consists of informational and practical blocks. The information block includes news and announcements, a brief description of the course, its curriculum, evaluation criteria, information about the author of the course, links to printed Internet sources and other literature sources necessary to do the course according to the electronic catalog of the library of UEPA. The practical block contains sections where various tasks are presented, for example, laboratory and practical assignments, materials for seminar classes and related topics, workbooks and tasks for conducting laboratory classes, control tasks and tests. In addition, methodological recommendations, lecture abstracts and presentations, etc. are offered for students’ consideration. Feedback between students and the teacher within a distance learning course is carried out with the help of the "Assignment" tool, which is used to ensure the submission of any completed work electronically. The teacher examines the received materials and assigns points or returns them with the indicated shortcomings for revision, which is also provided for in distance learning. The results of the assessment of students’ achievements are recorded in the electronic journal. Therefore, the experience of using distance learning at UEPA is valuable, as it makes it possible to fully implement the educational process in accordance with the curricula and training programs, and foster the development of the necessary competences indicated in the programs.